Imaging of gliomas at 1.5 and 3 Tesla - A comparative study. Issue 6 (18th December 2014) - Tselikas, Lambros; Souillard-Scemama, Raphaëlle; Naggara, Olivier; Mellerio, Charles; Varlet, Pascale; Dezamis, Edouard; Domont, Julien; Dhermain, Frédéric; Devaux, Bertrand; Chrétien, Fabrice; Meder, Jean-François; Pallud, Johan; et al.
Abstract: Background: Glioma follow-up is based on MRI parameters, which are correlated with survival. Although established criteria are used to evaluate tumor response, radiological markers may be confounded by differences in instrumentation including the magnetic field strength. We assessed whether MRIs obtained at 3 Tesla (T) and 1.5T provided similar information. Methods: We retrospectively compared imaging features of 30 consecutive patients with WHO grades II and III gliomas who underwent MRI at 1.5T and 3T within a month of each other, without any clinical changes during the same period. We compared lesion volumes on fluid attenuation inversion recovery (FLAIR), ratio of cerebral blood volume (rCBV) on perfusion-weighted imaging, contrast-to-noise ratio (CNR) on FLAIR, and on post-gadolinium 3D T1-weighted sequences between 1.5T and 3T using intraclass correlation coefficient (ICC). Concordance between observers within and between modalities was evaluated using weighted-kappa coefficient (w κ). Results: The mean ± SD delay between modalities (1.5T and 3T MRI) was 8.6 ± 5.6 days. Interobserver/intraobserver concordance for lesion volume was almost perfect for 1.5T (ICC = 0.96/0.97) and 3T (ICC = 0.99/0.98). Agreement between observers for contrast enhancement was excellent at 1.5T (w κ = 0.92) and 3T (w κ = 0.92). The tumor CNR was significantly higher for FLAIR at 1.5T ( P < .001), but it was higher at 3T ( P = .012) for contrast enhancement. Correlations between modalities for lesion volume (ICC = 0.97) and for rCBV values (ICC = 0.92) were almost perfect. Conclusions: In the follow-up of WHO grades II and III gliomas, 1.5T and 3T provide similar MRI features, suggesting that monitoring could be performed on either a 1.5 or a 3T MR magnet.